The Role of Positive Emotion as a Mediator between Psychological Capital and Work Engagement - Nerinda Rizky Firdaus (Universitas Ahmad Dahlan, 2019)
This research aimed to examine the role of positive emotions as a mediator between psychological capital and work engagement. This research conducted on 129 employees in Surabaya using convenience sampling technique. This study used a quantitative approach through surveys by collecting data using UWES (Utrecht Work Engagement Scale), PCQ (Psychological Capital Questionnaire) and PANAS (Positive Affect and Negative Affect Schedule).Â Path analysis was used to examine the relationship between the variables. The results showed that positive emotion doesnâ€™t have a role as a mediator in the relationship between psychological capital and work engagement. These findings indicated that employees with hope, optimism, self-efficacy, and resilience are able to generate vigor, dedication, and absorption in their work without experiencing positive emotion. The implication of this research concluded that the company needs to cultivate hope, optimism, self-efficacy, and resilience to employees so that employees have the vigor, dedication, and absorption on their work.